Computational approaches from polymer physics to investigate chromatin folding. (June 2020) - Bianco, Simona; Chiariello, Andrea M.; Conte, Mattia; Esposito, Andrea; Fiorillo, Luca; Musella, Francesco; Nicodemi, Mario
Abstract: Microscopy and sequencing-based technologies are providing increasing insights into chromatin architecture. Nevertheless, a full comprehension of chromosome folding and its link with vital cell functions is far from accomplished at the molecular level. Recent theoretical and computational approaches are providing important support to experiments to dissect the three-dimensional structure of chromosomes and its organizational mechanisms. Here, we review, in particular, the String&Binders polymer model of chromatin that describes the textbook scenario where contacts between distal DNA sites are established by cognate binders. It has been shown to recapitulate key features of chromosome folding and to be able at predicting how phenotypes causing structural variants rewire the interactions between genes and regulators.